1999
DOI: 10.1038/7023
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant, fully human monoclonal antibody with antitumor activity constructed from phage-displayed antibody fragments

Abstract: A single-chain Fv antibody fragment specific for the tumor-associated Ep-CAM molecule was isolated from a semisynthetic phage display library and converted into an intact, fully human IgG1 monoclonal antibody (huMab). The purified huMab had an affinity of 5 nM and effectively mediated tumor cell killing in in vitro and in vivo assays. These experiments show that nonimmunized phage antibody display libraries can be used to obtain high-affinity, functional, and clinically applicable huMabs directed against a tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 40 publications
0
53
0
Order By: Relevance
“…48 Interestingly, some reports have indicated that HAMA has little adverse effect on the overall clinical outcome of the mAb therapy; 49,50 however, reduction in toxicity will be of benefit as would increased persistence of the immune conjugate. Our use of a human IgG should limit immune reaction against the fusion protein 51 and although the scFv is murine, techniques to humanize this part of the construct such as the use of human phage libraries 52 could be used. In addition, genetic delivery of the immune conjugates will take full advantage of the relatively small size of the molecules for good tumor penetration and should also be able to circumvent the potential disadvantages of rapid clearance from the blood plasma.…”
Section: Discussionmentioning
confidence: 99%
“…48 Interestingly, some reports have indicated that HAMA has little adverse effect on the overall clinical outcome of the mAb therapy; 49,50 however, reduction in toxicity will be of benefit as would increased persistence of the immune conjugate. Our use of a human IgG should limit immune reaction against the fusion protein 51 and although the scFv is murine, techniques to humanize this part of the construct such as the use of human phage libraries 52 could be used. In addition, genetic delivery of the immune conjugates will take full advantage of the relatively small size of the molecules for good tumor penetration and should also be able to circumvent the potential disadvantages of rapid clearance from the blood plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-Ep-CAM scFv C28 was derived from scFv UBS-54, which was isolated from a semi-synthetic phage antibody display library in a pHEN vector (Huls et al, 1999). An SfiI/NotI fragment encoding the scFv C28 was isolated from the pHEN vector and cloned into the eukaryotic expression vector, pSTCF (Arafat et al, 2000), containing a secretion signal and a myc-and 6His-tag.…”
Section: Construction Of Pc28-gushmentioning
confidence: 99%
“…Having taken this into consideration (33,38), the in vitro cytotoxicity of anti-EpCAM(scFv)-MAP was determined using an XTT cell viability assay. Anti-EpCAM(scFv)-MAP showed specific toxicity toward L3.6pl and A431 cells reaching IC 50 values of 43 nmol/L and 67 nmol/L, respectively (Fig.…”
Section: Cytotoxicity Of Anti-epcam(scfv)-map In Vitromentioning
confidence: 99%